Situation Report: Romania, 23 September 1980 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romania Cautions against Interference in Poland Ceausescu's Speech Recalls Polish Themes The Travels of Vasile Pungan and Afghanistan Romania to Cut Defense Spending Why Is Coal Production Falling Short of Target? 15th International Historians' Congress: Scholarship and Propaganda